My Life Bits: A PERSONAL DATABASE FOR EVERYTHING. - Gemmell, Jim; Bell, Gordon; Lueder, Roger (Communications of the ACM, 2006)
The article presents the author's description of the development of software, MyLifeBits, for recording, storing, and accessing a personal lifetime archive. Memex, a personal information system, served as the blueprint for MyLifeBits with links and comments holding a central role. Faced with folders full of documents, messages, phone calls, photos, and music files, with inherent or potential metadata such as author, camera, comments, location, and time, the author and his team needed a framework to hold and link all of these objects in the Web. They deemed search to be the most critical requirement. In the process it was realized that metadata is often a key part of user recall. MyLifeBits has at its heart a SQL Server database that can store content and metadata for a variety of item types, including contacts, documents, email, events, photos, music and video. Currently their database supports 25 item types. Each item has about 20 common attributes. Additionally, each has a database table. For example, contacts have an additional 62 attributes, including email address and date of birth